2024
DOI: 10.1021/acs.jpca.3c08286
|View full text |Cite
|
Sign up to set email alerts
|

Carbon Atom Condensation on NH3–H2O Ices. An Alternative Pathway to Interstellar Methanimine and Methylamine

Germán Molpeceres,
Masashi Tsuge,
Kenji Furuya
et al.

Abstract: The recent discovery of the nature and behavior of carbon atoms interacting with interstellar ices has prompted a number of investigations on the chemistry initiated by carbon accretion on icy interstellar dust. In this work, we expand the range of processes promoted by carbon accretion to the chemistry initiated by the interaction of this atom with ammonia (NH 3 ) using quantum chemical calculations. We found that carbon addition to the ammonia molecule forms a rather stable radical, CNH 3 , that is easily hy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 91 publications
0
1
0
Order By: Relevance
“…Indeed, reactivity of radicals with molecular hydrogen has been shown to outweigh that of atomic hydrogen, despite the usual presence of activation barriers. Interestingly, HNC was not observed in the experiments by Borget et al, which can be explained by the reaction 7 having a barrier of 56–70 kJ mol –1 in the gas phase. , Recently, Molpeceres et al demonstrated that hydrogenation and H-abstraction reactions on the intermediate formed after the chemisorption of carbon atoms on ammonia in water ices lead to a competition between the formation of CH 3 NH 2 and the isomers HCN and HNC.…”
mentioning
confidence: 99%
“…Indeed, reactivity of radicals with molecular hydrogen has been shown to outweigh that of atomic hydrogen, despite the usual presence of activation barriers. Interestingly, HNC was not observed in the experiments by Borget et al, which can be explained by the reaction 7 having a barrier of 56–70 kJ mol –1 in the gas phase. , Recently, Molpeceres et al demonstrated that hydrogenation and H-abstraction reactions on the intermediate formed after the chemisorption of carbon atoms on ammonia in water ices lead to a competition between the formation of CH 3 NH 2 and the isomers HCN and HNC.…”
mentioning
confidence: 99%